MULTI CRITERIA ANALYSIS MENENTUKAN POINT WEIGHT COMPARATION DALAM PENETAPAN DECISION PRIORITY - Akmaludin, Akmaludin (Jurnal Pilar Nusa Mandiri, 2015)
Decision-making method being used in the Analytic Hierarchical Process (AHP), each method has different characteristics, it can be seen from how the data acquisition was doing, whether using a single data or data groups, then how to determine the scale that will be used , and how the determination of the amount to be entered into pairwise matrix. Each method has its own way and each method will yield the amount of different values, but about priorities can result in the same decision. In this paper will try to discuss the differences in data processing, the methods used, the determination of pairwise matrix and the resulting acquisition priorities. Multi Criteria Analysis (MCA) provides an overview of the differences produced by these methods